Perlawanan Perempuan Adat Wana Posangke dalam Mempertahankan Identitas Kultural - Zaiful Zaiful; Roslinawati Roslinawati; Hasan Muhammad; Surahman Cinu (HUMANISMA : Journal of Gender Studies, 2020)
Customary land is claimed as a safekeeping of history that must be maintained, local wisdom is considered as a code of conduct, and forests and traditional land as a dependent space for communal living. Meanwhile, the pace of expansion of palm oil plantations by the private sector supported by the state through permit schemes has created resource conflicts in customary law areas that threaten the existence of Tau Taa Wana's cultural heritage. This threat to cultural heritage has pushed the indigenous women of Wana Posangke to carry out resistance movements to protect and maintain communal cultural identity. This means that expansion activities that threaten the existence of cultural heritage encourage the desire to protect and maintain cultural heritage.